Prevalence of Musculoskeletal Disorders in Rural Women in Qazvin Province - Elham Attari; Faezeh Masoumi; Abbas Alaei Moghadam; Azam Abdollahpour (Biyumikānīk-i varzishī)
Objective: In a fast-paced world of technology that is changing people’s lifestyles and reducing mobility, rural women who were once a model of mobility have not been spared. This study aimed to investigate the prevalence of musculoskeletal abnormalities of the upper and lower limbs in rural women in Qazvin province. Methods: The present study was a descriptive-comparative study. The statistical population of this study was rural women in Qazvin province with an age range of 15-65 years and an average age (41.88±15.70). In this research, 3023 people participated and were divided into four groups with different age ranges. Subjects were selected by snowball sampling method and participated in the study voluntarily. The collection tools included consent form, musculoskeletal abnormalities registration form, caliper, vertical line, checkerboard, and New York test. Descriptive statistics were used to show the prevalence of anomalies, and the Kruskal-Wallis test was used for group comparison in SPSS software v. 24. Results: Kruskal-Wallis test showed that in the variables head forward (P=0.001), torticollis (P=0.001), shoulder forward (P=0.008), uneven shoulder (P=0.001), kyphosis (P=0.001), lordosis (P=0.001), flat back (P=0.003), scoliosis (P=0.001), anterior pelvic rotation (P=0.001), genu Varum (P=0.001), genu valgum (P=0.001), genu recurvatum (P=0.001), flat foot (P=0.008), Pes cavus (P=0.004) and hallux valgus (P=0.001). There was a significant difference between groups. Also, the highest prevalence of upper limb deformities was related to uneven shoulder, head forward, and lordosis. The highest prevalence of lower limb deformities was related to anterior pelvic rotation, genu valgum, and flat foot. Conclusion: The results show that the prevalence of musculoskeletal abnormalities of the upper and lower limbs in rural women in Qazvin province is highly prevalent in the age range of 35-31 years and 50-36 years. Therefore, researchers believe that providing information about the prevalence of postural disorders can effectively design preventive programs and emphasize the need to develop corrective exercise and rehabilitation programs for this segment of society.